Quantitative analysis of pore evolution and its application in basin simulation:A case study of Chang 6 reservoir in Heshui area, Ordos Basin, NW China - Ting Shang; Meijuan Chu; Xiaolei Zhang; Bin Wang; Jihong Li; Huiruo Zhang; Zhongyi Zhang; Xin Liu (Energy Geoscience)
In recent years, fueled by significant advancements in oil exploration technologies within the Ordos Basin, an increasing number of low-permeability or ultra-low-permeability reservoirs have been identified. Elucidating their reservoir characteristics and formation mechanisms has become a critical priority for sustainable hydrocarbon development. The study focused on the Chang 6 Member of the Upper Triassic Yanchang Formation in the Heshui area of the Ordos Basin, systematically investigating its petrological features, porosity and permeability characteristics, diagenesis, and diagenetic evolution sequence. By integrating core observation, thin-section identification, and physical property measurements, a comprehensive quantitative evaluation of reservoir pore evolution was performed. These analytical outcomes were subsequently applied to simulate hydrocarbon migration and accumulation. These research results will provide a scientific basis for in-depth quantitative study of the pore evolution in ultra-low-permeability oil reservoirs and accurately constructing basin models. As indicated, the reservoir lithology in the study area predominantly comprises siltstone interbedded with mudstone or argillaceous siltstone, characterized by low porosity and permeability. Through diagenetic characteristics-based reconstruction constrained by the existing porosity data, pore evolution during diagenesis was quantitatively modeled. The simulated pore evolution aligns with actual geological observations, validating the reliability of the methodology. Furthermore, the quantified pore evolution results were applied to simulate hydrocarbon migration using PetroMod software, showing that hydrocarbon charging in the basin began at the end of the Late Jurassic (J3), peaking in hydrocarbon generation, expulsion, and accumulation by the end of the Early Cretaceous (K1) and maintaining high accumulation rates until the late Cretaceous, though significantly decreasing at the present stage. The simulation results were verified by comparison with actual drilling data, which confirms their reliability and applicability to other analogous oilfields.